(untitled) (American Journal of Technology and Applied Sciences, 2025)
The incidence of breast cancer among women aged 20–40 has shown a significant upward trend over the past two decades, making early-onset breast malignancies an emerging global health challenge. This article examines the multifactorial risk determinants contributing to this rise, including genetic predisposition, lifestyle and environmental exposures, reproductive patterns, and hormonal influences. Modern diagnostic advances such as breast MRI, high-resolution ultrasound, molecular profiling, artificial intelligence–assisted imaging and liquid biopsy technologies are analyzed as key tools for early and precise detection in younger patients.